Professor Knight's Note on Interest Theory - Lange, Oskar (Review of Economic Studies, 1937)
Professor Knight's Note on Interest Theory Get access Oskar Lange Oskar Lange London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 4, Issue 3, June 1937, Pages 231–235, https://doi.org/10.2307/2967458 Published: 01 June 1937